Twitter Analysis on Waqf and Health - Aziza, Asyifa Nur (International Journal of Waqf, 2023)
This study aims to observe the evolution of public sentiment towards waqf health around the world. This research approach uses primary data by taking samples from Twitter tweets during the period 2011-2023. Sentiment analysis was conducted using VADER Python programming to classify sentiment into positive, negative and neutral. The results showed that India was the country with the largest distribution of tweet data discussing the issue of waqf health. Furthermore, positive sentiments dominate the discussion on the Twitter platform, reaching 63.2% of the total sentiments expressed. On the other hand, negative sentiments took second place with a contribution of 21.1%. Although neutral sentiment was the least, it still accounted for 15.8% of the total sentiment expressed in the discussion. Through this approach, this research provides a more in-depth picture of how people's views on waqf health evolve over time. This sentiment data can serve as a basis for further understanding of the global perception of waqf health initiatives